The Impact of ICT Towards Saudi EFL Students’ Writing Skills: A Quasi-Experimental Study - Abdullahi Salisu Kademi (Universitas Negeri Makassar, 2021)
This study aimed to investigate the impact of using the word processor application on the writing achievement of Saudi EFL learners at Jubail Technical Institute. It used embedded-experimental mixed methods research design in which the qualitative data set provides an auxiliary role in a study that is primarily quantitative. Nested sampling technique was used to select participants for both the dominant quantitative and the auxiliary qualitative phases of the study. The participants were divided into two groups: the experimental group, which studied writing using the word processor, and the control group, which learnt writing using the traditional method. It was hypothesized that the experimental group participants would have a higher achievement in a writing performance test than those of the control group. After establishing that the two groups had homogenous writing abilities before the treatment, post-test results showed that the experimental group participants had a statistically significantly higher achievement in the writing performance test (t(67) = 6.21, p < .001) than the control group. The study recommended introducing computer-assisted writing programs in composition classes and training teachers on how to use such programs to help students develop their writing skills.